2015
DOI: 10.1152/ajpgi.00289.2014
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Gab1 adaptor protein in hepatocytes aggravates experimental liver fibrosis in mice

Abstract: Grb2-associated binder 1 (Gab1) adaptor protein amplifies signals downstream of a broad range of growth factors/receptor tyrosine kinases. Although these signals are implicated in liver fibrogenesis, the role of Gab1 remains unclear. To elucidate the role of Gab1, liver fibrosis was examined in hepatocyte-specific Gab1-conditional knockout (Gab1CKO) mice upon bile duct ligation (BDL). Gab1CKO mice developed exacerbated liver fibrosis with activation of hepatic myofibroblasts after BDL compared with control mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Total RNA was extracted using a Qiagen (Hilden, Germany) QIAshredder and an RNA‐easy Mini kit according to the manufacturer's instructions. Reverse transcription–polymerase chain reaction (RT‐PCR) and real‐time PCR were carried out as described previously . The Quantitect gene assay kit (Qiagen) was used for the analysis of human FoxM1, and glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted using a Qiagen (Hilden, Germany) QIAshredder and an RNA‐easy Mini kit according to the manufacturer's instructions. Reverse transcription–polymerase chain reaction (RT‐PCR) and real‐time PCR were carried out as described previously . The Quantitect gene assay kit (Qiagen) was used for the analysis of human FoxM1, and glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes were isolated from control and Gab1 CKO mice using the two‐step pronase‐collagenase perfusion method and cultured as described . Hepatocyte preparations with viability of 90% or higher, as determined by trypan blue exclusion, were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that Gab1 regulates mouse embryo development through these pathways in vivo . More recently, we demonstrated that in hepatocytes Gab1 is essential for protection against liver fibrogenesis in mice . Furthermore, others have shown that Gab1 promotes hepatocyte proliferation after partial hepatectomy in mice, indicating that Gab1 is crucial for the repair process following liver injury.…”
mentioning
confidence: 89%
“…FGF-1 is able to decrease collagen production and α-SMA expression on fibroblasts, partially inhibit TGF-β and reverse TGF-β-induced EMT [123,124], Grb2-associated binder 1 (Gab1) adaptor protein is a docking protein that interacts with receptor tyrosine kinases, amplifying growth factor signals [125]. In an animal model of liver fibrosis, Kizu et al showed that Gab1-conditional knockout mice developed severe liver fibrosis, indicating a possible antifibrotic or homeostatic role of Gab-1 [126]. …”
Section: Immune Responses In Fibrotic Processmentioning
confidence: 99%